TINGKAT DAYA SAING EKONOMI DAERAH KABUPATEN JENEPONTO - Saparuddin M (Fakultas Ekonomi Universitas Negeri Jakarta, 2016)
Abstract Problems in the study that the lift is the extent to which the advantages of each economic indicator that could support the policy direction of regional economic competitiveness Jeneponto. The research method used is descriptive analysis. By describing each economic variables. The research results are obtained is found that the competitiveness of economic variables in Jeneponto still show low levels of competitiveness in comparison with other districts in South Sulawesi province. This can be seen from almost all economic sectors in Jeneponto ratio or index of economic variables at the bottom compared to other districts in South Sulawesi province. Keyword : Daya saing ekonomi, sektor ekonomi